Pengembangan E-Modul Berbasis Electronic Publication (EPUB) Menggunakan Model Pengembangan ADDIE Pada Mata Pelajaran Pemrograman Dasar di SMK Negeri 4 Malang - Andre Diofanu; Satrio Hadi Wijoyo; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The purpose of this research is to ameliorate the ongoing learning process in Class ten, Department of Multimedia at the State Vocational School 4 Malang, that is focused on the teacher-centered approach, whereby the teacher is actively involved in sharing information using power media, and the learners are in a receptive mode and only notes down everything. The development of this E-Module, it is expected to increase students' motivation and understanding. The basic development model is the ADDIE model modified by Molenda. The data collection techniques involve instruments in the form of questions Pre-test and Post-test. Data processing techniques using the Kolmogorov-Smirnov Test and Wilcoxon Test to test hypotheses based on research data obtained. The results of the analysis process show that the development of E-Modules is needed due to the lack of learning media that can support the learning process. The results of the design process are wireframe and the draft Learning Implementation Plan. The results of the development process are videos, E-Module, and the results of the validation on the material, media, and instruments where getting valid average results. The results of the implementation process are in the form of students' pre-test and post-test scores. The results of the evaluation process show high effectiveness and high efficiency based on the results of the average student response questionnaire which was worth 82.77 percent.